Adhesive composition, adhesive, adhesive tape, and airtight, waterproof adhesive tape

JP7643451B2Active Publication Date: 2025-03-11MITSUBISHI CHEM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022510535
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-27
Filing Date
2021-03-23
Publication Date
2025-03-11
Estimated Expiration
2041-03-23

AI Technical Summary

Benefits of technology

【0010】 本発明は、(メタ)アクリル酸モノマー(a1)単位および水酸基含有モノマー(a2)単位を含むアクリル系樹脂(A)と、エポキシ系架橋剤(b1)と、イソシアネート系架橋剤(b2)と、難燃剤(C)とを含有する粘着剤組成物であることから、通常、架橋剤としてエポキシ系架橋剤(b1)またはイソシアネート系架橋剤(b2)のどちらか一方を含有する粘着剤組成物では難燃剤を添加しても、難燃性の改善は限定的で、欧州建材火災安全規格 EN13501-1(EN規格)の難燃性を満足することができないのに対して、本発明の粘着剤組成物は難燃性の改善効果が大きくEN規格の難燃性を満足することができ、架橋剤のどちらか一方を含有する粘着剤組成物に難燃剤を添加した時と比べ、予想を大幅に上回る難燃性を付与することができる。また、一般に、難燃剤を添加すると、粘着テープの保持力が大幅に低下するところ、高い難燃性を有しながら、粘着力、保持力の両方に優れるものである。そのため、それを用いてなる粘着剤および粘着テープとして有用であり、例えば、建設用に用いられる粘着テープとして好適に用いることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643451000001
    Figure 0007643451000001
  • Figure 0007643451000002
    Figure 0007643451000002
  • Figure 0007643451000003
    Figure 0007643451000003
Patent Text Reader

Abstract

Provided is an adhesive composition that is highly flame retardant but has excellent adhesive force and holding force and an excellent balance of adhesive properties. The adhesive composition contains an acrylic resin (A) that includes a (meth)acrylate monomer (a1) unit and a hydroxyl group–containing monomer (a2) unit, an epoxy cross-linking agent (b1), an isocyanate cross-linking agent (b2), and a flame retardant (C).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition, and more specifically, to an adhesive composition which contains a flame retardant and has high flame retardancy while also exhibiting excellent adhesion and holding power, whereas the addition of a flame retardant usually results in a significant decrease in the holding power of an adhesive tape, and to an adhesive, adhesive tape, and airtight waterproof adhesive tape which use the same. [Background technology]

[0002] Conventionally, flame retardant adhesive tapes have been developed by adding flame retardants to the adhesive layer. For example, Patent Document 1 discloses a flame-retardant adhesive tape for electrical insulation that is excellent in flame retardancy, adhesive properties, and carbonization insulation breakdown suppression by using an isocyanate-based crosslinking agent as a crosslinking agent for an acrylic resin and adding a phosphoric acid ester amide-based flame retardant to the flame retardant. Also, an epoxy-based compound is exemplified as a crosslinking agent. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2008-24827 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the adhesive tape disclosed in the above Patent Document 1 is for electrical insulation purposes, and its adhesive strength is insufficient for use as an adhesive tape for construction purposes, which requires even stronger adhesive strength.

[0005] In addition, adhesive strength can be improved by reducing the amount of crosslinking agent, but adding a flame retardant usually results in a significant decrease in holding power, so there has been a demand for an adhesive tape that contains a flame retardant and has high flame retardancy, yet has excellent both adhesive strength and holding power.

[0006] In view of this background, the present invention provides a pressure-sensitive adhesive composition that has excellent adhesion and holding power while also having high flame retardancy, by combining an epoxy-based crosslinking agent and an isocyanate-based crosslinking agent as crosslinking agents with a specific acrylic resin.

[0007] On the other hand, the acrylic adhesive composition is also useful as an airtight waterproof adhesive tape, and in response to the enforcement of the Act on Promotion of Quality of Waterproof / Airtight Houses (Houses with Excellent Waterproofing and Airtightness) and energy saving associated with high airtightness and high insulation of houses, airtight waterproof adhesive tapes for at least one of airtightness and waterproofing are used in gaps between the structures and members of houses and between members (mainly around sash openings and joints of overlapping parts of moisture-permeable waterproof sheets, etc.). Such airtight waterproof adhesive tapes are required to firmly adhere to adherends with relatively high polarity such as aluminum sashes, adherends with relatively low polarity such as moisture-permeable waterproof sheets, and rough surfaces such as OSB boards (Oriented Strand Board: wood boards made by aligning thin shaved wood pieces, laminating them, and compressing them at high temperature with an adhesive), and are also required to have high holding power so that moisture-permeable waterproof sheets fixed with the tape do not slip, and are also required to have high flame retardancy. [Means for solving the problem]

[0008] However, the present inventors have conducted extensive research in light of these circumstances and have found that, in an adhesive composition using an acrylic resin, when the copolymerization components constituting the acrylic resin contain a (meth)acrylic acid monomer and a hydroxyl group-containing monomer, and when the copolymerization components contain both an epoxy-based crosslinking agent and an isocyanate-based crosslinking agent together with a flame retardant, an adhesive composition having excellent adhesive strength and holding strength while also having high flame retardancy can be obtained, as well as an adhesive, adhesive tape, and airtight waterproof adhesive tape made using the same.

[0009] That is, the gist of the present invention is as follows. <1> A pressure-sensitive adhesive composition comprising an acrylic resin (A) containing (meth)acrylic acid monomer (a1) units and hydroxyl group-containing monomer (a2) units, an epoxy-based crosslinking agent (b1), an isocyanate-based crosslinking agent (b2), and a flame retardant (C). <2> The acrylic resin (A) contains a terminal carboxyl group-containing monomer (a3) ​​unit represented by the following general formula (1): <1> The pressure-sensitive adhesive composition according to claim 1. [ka] Here, R 1 is hydrogen or a methyl group, R 2 represents a divalent saturated aliphatic group, an unsaturated aliphatic group, an aromatic group, a saturated alicyclic group, or an unsaturated alicyclic hydrocarbon group, and n represents a positive number of 1 or more. <3> The acrylic resin (A) is an acrylic resin having the following monomer units (a1) to (a4): <2> The pressure-sensitive adhesive composition according to claim 1. (a1) (meth)acrylic acid monomer unit 0.1 to 5% by weight (a2) Hydroxyl group-containing monomer unit: 0.01 to 5% by weight (a3) 1 to 20% by weight of a terminal carboxyl group-containing monomer unit represented by the above general formula (1) (a4) 55 to 97% by weight of (meth)acrylate monomer units having an alkyl group having 4 to 24 carbon atoms <4> The content of the flame retardant (C) is 1 to 100 parts by weight per 100 parts by weight of the acrylic resin (A). <1> ~ <3> 13. The pressure-sensitive adhesive composition according to any one of claims 1 to 12. <5> <1> ~ <4> 2. A pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition according to any one of the preceding claims. <6> A substrate and a film formed on the substrate. <5> 2. An adhesive tape comprising the adhesive according to claim 1. <7> <6> An airtight and waterproof adhesive tape comprising the adhesive tape described above. Effect of the Invention

[0010] The present invention is an adhesive composition containing an acrylic resin (A) containing a (meth)acrylic acid monomer (a1) unit and a hydroxyl group-containing monomer (a2) unit, an epoxy crosslinking agent (b1), an isocyanate crosslinking agent (b2), and a flame retardant (C). In general, when a flame retardant is added to an adhesive composition containing either an epoxy crosslinking agent (b1) or an isocyanate crosslinking agent (b2) as a crosslinking agent, the improvement in flame retardancy is limited, and the flame retardancy of the European building material fire safety standard EN13501-1 (EN standard) cannot be satisfied. On the other hand, the adhesive composition of the present invention has a large improvement effect on flame retardancy and can satisfy the flame retardancy of the EN standard, and can impart flame retardancy that is significantly higher than expected compared to when a flame retardant is added to an adhesive composition containing either one of the crosslinking agents. In addition, while the holding power of an adhesive tape is generally significantly reduced when a flame retardant is added, the adhesive composition of the present invention has excellent adhesion and holding power while having high flame retardancy. Therefore, the adhesive and adhesive tape using the same are useful, and can be suitably used, for example, as an adhesive tape for construction use.

[0011] In the present invention, when the acrylic resin (A) is a pressure-sensitive adhesive composition containing a terminal carboxyl group-containing monomer (a3) ​​unit represented by the following general formula (1), the pressure-sensitive adhesive composition has good flame retardancy and an excellent balance of adhesion and holding power to an adherend. [ka] Here, R 1 is hydrogen or a methyl group, R 2 represents a divalent saturated aliphatic group, an unsaturated aliphatic group, an aromatic group, a saturated alicyclic group, or an unsaturated alicyclic hydrocarbon group, and n represents a positive number of 1 or more.

[0012] In the present invention, in particular, when the acrylic resin (A) is an acrylic resin having monomer units (a1) to (a4) below, the pressure-sensitive adhesive composition can have better adhesion and holding power to an adherend. (a1) (meth)acrylic acid monomer unit 0.1 to 5% by weight (a2) Hydroxyl group-containing monomer unit: 0.01 to 5% by weight (a3) 1 to 20% by weight of a terminal carboxyl group-containing monomer unit represented by the above general formula (1) (a4) 55 to 97% by weight of (meth)acrylate monomer units having an alkyl group having 4 to 24 carbon atoms

[0013] In particular, in the pressure-sensitive adhesive composition of the present invention, when the content of the flame retardant (C) in the pressure-sensitive adhesive composition is 1 to 100% by weight, the pressure-sensitive adhesive composition can have a better balance of adhesion and holding power to the adherend. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below. In the present invention, "(meth)acrylic" means acrylic or methacrylic, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylate" means acrylate or methacrylate. The acrylic resin is a resin obtained by polymerizing a copolymerization component containing at least one (meth)acrylate monomer.

[0015] The pressure-sensitive adhesive composition of the present invention contains an acrylic resin (A) having structural units derived from a specific monomer, i.e., a specific monomer unit.

[0016] <Acrylic resin (A)> The acrylic resin (A) used in the present invention has (meth)acrylic acid monomer (a1) units and hydroxyl group-containing monomer (a2) units. In addition to the monomers (a1) and (a2), the acrylic resin (A) preferably has monomer (a3) ​​units, more preferably monomer (a4) units, and if necessary, further has monomers (a5) to (a6) units. Each monomer unit will be described below.

[0017] [Monomer (a1) unit] The content of the (meth)acrylic acid monomer (a1) unit is usually 0.1 to 5% by weight, particularly 0.5 to 4.5% by weight, and more preferably 1 to 4% by weight, of the entire acrylic resin (A). If the content is too low, the adhesiveness tends to decrease, whereas if it is too high, the viscosity of the coating liquid increases, tending to deteriorate the coatability.

[0018] [Monomer (a2) unit] Examples of copolymerizable monomers for forming the hydroxyl group-containing monomer (a2) units include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; caprolactone-modified monomers such as caprolactone-modified 2-hydroxyethyl (meth)acrylate; oxyalkylene-modified monomers such as diethylene glycol (meth)acrylate and polyethylene glycol (meth)acrylate; primary hydroxyl group-containing monomers such as 2-acryloyloxyethyl-2-hydroxyethyl phthalate; secondary hydroxyl group-containing monomers such as 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate; and tertiary hydroxyl group-containing monomers such as 2,2-dimethyl-2-hydroxyethyl (meth)acrylate.

[0019] Among these, primary hydroxyl group-containing monomers are preferred because of their excellent reactivity with crosslinking agents, and in particular, hydroxyalkyl (meth)acrylates, 2-hydroxyethyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate are preferred.

[0020] The hydroxyl group-containing monomer (a2) unit is useful because it becomes a crosslinking point with the isocyanate-based crosslinking agent (b2). The hydroxyl group-containing monomer (a2) unit is usually 0.01 to 5% by weight, particularly 0.05 to 3% by weight, and more preferably 0.05 to 2% by weight, based on the total acrylic resin (A). If the monomer (a2) unit is too small, the holding power tends to decrease, and if it is too large, the adhesiveness tends to decrease.

[0021] [Monomer (a3) ​​unit] The monomer (a3) ​​unit of the present invention is a terminal carboxyl group-containing monomer unit represented by the following general formula (1).

[0022] [ka] Here, R 1 is hydrogen or a methyl group, R 2 represents a divalent saturated aliphatic group, an unsaturated aliphatic group, an aromatic group, a saturated alicyclic group, or an unsaturated alicyclic hydrocarbon group, and n represents a positive number of 1 or more.

[0023] Above R 1 is preferably hydrogen, R 2 The hydrocarbon is usually preferably an alkylene, such as a methylene group, having 1 to 10 carbon atoms, more preferably 1 to 5, and particularly preferably 1 to 2 carbon atoms, such as phenyl, phenylene, or further preferably ethylene, and the above n is preferably 1 to 10, more preferably 1 to 5, particularly preferably 1 to 3, and particularly preferably 1 to 2, and may have a combination of these.

[0024] The content of the monomer (a3) ​​unit in the acrylic resin (A) is usually 1 to 20% by weight, particularly 1.5 to 15% by weight, and more preferably 2 to 8.5% by weight. If the content is too low or high, the adhesiveness tends to decrease.

[0025] The acrylic resin (A) having the monomer (a3) ​​unit can be obtained by polymerization using a monomer represented by the following chemical formula (2) as a copolymerizable monomer. [Formula] CH2=CR 1 -CO-O-(R 2 -COO-) n H (2) (where R 1 is hydrogen or a methyl group, R 2 represents a divalent saturated aliphatic group, an unsaturated aliphatic group, an aromatic group, a saturated alicyclic group, or an unsaturated alicyclic hydrocarbon group, and n represents a positive number of 1 or more.

[0026] The ratio of the monomer (a3) ​​units to the monomer (a1) units is preferably, by weight, usually 10 to 400 parts by weight, particularly 20 to 200 parts by weight, further 25 to 100 parts by weight, and particularly 30 to 75 parts by weight, of the monomer (a1) units per 100 parts by weight of the monomer (a3) ​​units. If the amount of the monomer (a1) units is too small, the holding power tends to decrease, whereas if the amount is too large, the viscosity of the coating liquid increases, tending to deteriorate the coatability.

[0027] [Monomer (a4) unit] The acrylic resin (A) used in the present invention preferably further contains a (meth)acrylate monomer (a4) unit having an alkyl group having 4 to 24 carbon atoms. The copolymerizable monomer for forming the (meth)acrylate monomer (a4) unit having an alkyl group having 4 to 24 carbon atoms may be a (meth)acrylate monomer having any alkyl group having 4 to 24 carbon atoms, and it is particularly preferable to contain a (meth)acrylate monomer (a4-1) having an alkyl group having 4 to 7 carbon atoms and a (meth)acrylate monomer (a4-2) having an alkyl group having 8 to 24 carbon atoms.

[0028] Examples of the (meth)acrylate monomer (a4-1) having an alkyl group having 4 to 7 carbon atoms include n-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, etc. Among these, n-butyl (meth)acrylate is preferred because it is easily available and economically advantageous.

[0029] Examples of the (meth)acrylate monomer (a4-2) having an alkyl group having 8 to 24 carbon atoms include 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, isotridecyl (meth)acrylate, myristyl (meth)acrylate, isomyristyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, and behenyl (meth)acrylate. Among these, (meth)acrylates having an alkyl group having 8 to 12 carbon atoms are preferred because of their low polarity and low glass transition temperature, and 2-ethylhexyl (meth)acrylate is particularly preferred.

[0030] The content of the monomer (a4) unit is usually 55 to 97% by weight, particularly 70 to 95% by weight, and further preferably 80 to 93% by weight, of the entire acrylic resin (A). If the content is too low, the adhesiveness tends to decrease, whereas if the content is too high, the adhesiveness and holding power tend to decrease.

[0031] The ratio of the monomer (a4-1) units to the monomer (a4-2) units is usually (a4-1) / (a4-2)=1 / 99 to 85 / 15, preferably 2 / 98 to 75 / 25, more preferably 3 / 97 to 70 / 30, even more preferably 5 / 95 to 60 / 40, and even more preferably 5 / 95 to 45 / 55 by weight. If the ratio of the monomer (a4-1) units is too small, the holding power tends to decrease, whereas if it is too large, the adhesiveness tends to decrease.

[0032] [Monomer (a5) unit] The acrylic resin (A) used in the present invention preferably further contains (meth)acrylate monomer (a5-1) units having an alkyl group with 1 to 3 carbon atoms, cyclic structure-containing monomer (a5-2) units, or vinyl ester monomer (a5-3) units having 3 to 10 carbon atoms. The collective term for the above (a5-1) to (a5-3) is monomer (a5).

[0033] Examples of copolymerizable monomers for forming the (meth)acrylate monomer (a5-1) units having an alkyl group having 1 to 3 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, etc. Among these, methyl (meth)acrylate and ethyl (meth)acrylate are preferred.

[0034] The copolymerizable monomer for forming the cyclic structure-containing monomer (a5-2) unit is usually an acrylic monomer having a substituent containing a cyclic structure, and examples thereof include heterocycle-containing (meth)acrylates having a heterocycle such as a morpholine ring, a piperidine ring, a pyrrolidine ring, or a piperazine ring, such as N-(meth)acryloylmorpholine, N-vinylpyrrolidone, N-vinylcaprolactam, vinylpyrrolidone, N-(meth)acryloylpiperidine, and N-(meth)acryloylpyrrolidine, phenyl(meth)acrylate, phenoxyethyl(meth)acrylate, and phenyldiethylene glycol (meth)acrylate. ) acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, nonylphenol polyethylene glycol (meth)acrylate, nonylphenoxy polyethylene glycol (meth)acrylate, isobornyl (meth)acrylate, biphenyloxyethyl (meth)acrylate, and others, such as styrene and α-methylstyrene. Among them, heterocycle-containing (meth)acrylates having a morpholine ring are preferred because of their good balance of various physical properties, and N-(meth)acryloylmorpholine is particularly preferred because of its ease of availability and safety.

[0035] Examples of copolymerizable monomers for forming the vinyl ester monomer (a5-3) units having 3 to 10 carbon atoms include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, etc. Among these, vinyl acetate is preferred because of its easy availability.

[0036] The content of the monomer (a5) unit is usually 11% by weight or less, preferably 10% by weight or less, and particularly preferably 8% by weight or less, based on the total acrylic resin (A). If the content of the (a5) component is too high, the adhesiveness to the adherend tends to decrease. The lower limit of the content of the (a5) component in the copolymerization component (a) is 0% by weight, but is usually 1% by weight.

[0037] [Monomer (a6) unit] In the present invention, the copolymerizable monomer may have other copolymerizable monomer (a6) units as necessary. Examples of the copolymerizable monomer for forming the other copolymerizable monomer (a6) units include functional group-containing monomers such as acetoacetyl group-containing monomers, isocyanate group-containing monomers, glycidyl group-containing monomers, amino group-containing monomers, and amide group-containing monomers, as well as other copolymerizable monomers.

[0038] Examples of the acetoacetyl group-containing monomer include 2-(acetoacetoxy)ethyl (meth)acrylate and allyl acetoacetate.

[0039] Examples of the isocyanate group-containing monomer include 2-acryloyloxyethyl isocyanate, 2-methacryloyloxyethyl isocyanate, and alkylene oxide adducts thereof.

[0040] Examples of the glycidyl group-containing monomer include glycidyl (meth)acrylate and allyl glycidyl (meth)acrylate.

[0041] Examples of the amino group-containing monomer include monomers having an ethylenically unsaturated double bond and an amino group (unsubstituted or substituted amino group), such as mono-substituted amino group-containing (meth)acrylic acid esters of aminoalkyl (meth)acrylates such as aminomethyl (meth)acrylate, aminoethyl (meth)acrylate, aminopropyl (meth)acrylate, and aminoisopropyl (meth)acrylate, and (meth)acrylic acid esters of N-alkylaminoalkyl such as N-(t-butyl)aminoethyl (meth)acrylate; (meth)acrylic acid esters of N,N-dialkylaminoalkyl such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylate. disubstituted amino group-containing (meth)acrylic acid esters such as N,N-dimethylaminopropyl(meth)acrylamide; dialkylaminoalkyl(meth)acrylamides such as N,N-dimethylaminopropyl(meth)acrylamide, and quaternized salts of these amino group-containing monomers; amino group-containing styrenes such as p-aminostyrene; styrenes having a dialkylamino group such as 3-(dimethylamino)styrene and dimethylaminomethylstyrene; dialkylaminoalkyl vinyl ethers such as N,N-dimethylaminoethyl vinyl ether and N,N-diethylaminoethyl vinyl ether; allylamine, 4-diisopropylamino-1-butene, trans-2-butene-1,4-diamine, 2-vinyl-4,6-diamino-1,3,5-triazine, and the like.

[0042] The amide group-containing monomer includes a monomer having an ethylenically unsaturated double bond and an amide group (a group having an amide bond), such as (meth)acrylamide; N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, Nn-butyl(meth)acrylamide, N-isobutyl(meth)acrylamide, Ns-butyl(meth)acrylamide, Nt-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, da N-alkyl(meth)acrylamides such as acetone(meth)acrylamide, N,N'-methylenebis(meth)acrylamide, and N-(1,1-dimethyl-3-oxobutyl)(meth)acrylamide; N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, N,N-diisobutyl(meth)acrylamide, and N,N-di(s-butyl)(meth)acrylamide; amide, N,N-dialkyl (meth)acrylamides such as N,N-di(t-butyl) (meth)acrylamide, N,N-dipentyl (meth)acrylamide, N,N-dihexyl (meth)acrylamide, N,N-diheptyl (meth)acrylamide, N,N-dioctyl (meth)acrylamide, N,N-diallyl (meth)acrylamide, and N,N-ethylmethylacrylamide; dialkylaminoalkyl (meth)acrylamides such as N,N-dimethylaminopropyl (meth)acrylamide; N-vinylacetamide, N-vinyl phosphatase, and the like. Examples of such amide group-containing monomers include substituted amide group-containing monomers such as N-methylol (meth)acrylamide, (meth)acrylamide ethyl ethylene urea, and (meth)acrylamide-t-butylsulfonic acid; hydroxy group-containing (meth)acrylamides such as N-methylol (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, and N-methylolpropane (meth)acrylamide; alkoxy group-containing (meth)acrylamides such as N-methoxymethyl (meth)acrylamide and N-(n-butoxymethyl) (meth)acrylamide; and quaternized salts of these amide group-containing monomers.

[0043] Examples of the other copolymerizable monomers include monomers containing an alkoxy group or an oxyalkylene group, such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and polypropylene glycol mono(meth)acrylate; acrylonitrile, methacrylonitrile, vinyl stearate, vinyl chloride, vinylidene chloride, alkyl vinyl ether, vinyl toluene, dialkyl itaconate, dialkyl fumarate, allyl alcohol, acrylic chloride, methyl vinyl ketone, allyl trimethylammonium chloride, and dimethylallyl vinyl ketone.

[0044] The other copolymerizable monomers (a6) may be contained to such an extent that the effects of the present invention are not adversely affected, for example, 10% by weight or less, in order to adjust the physical properties according to the application. The lower limit is usually 0% by weight.

[0045] Thus, the acrylic resin (A) is obtained by polymerizing the above monomers (a1) and (a2), preferably the monomer (a3), more preferably the monomer (a4), and if necessary, the monomers (a5) to (a6). That is, the acrylic resin (A) is obtained which has the above monomer (a1) and (a2) units, preferably the monomer (a3) ​​unit, more preferably the monomer (a4) unit, and if necessary, the monomers (a5) to (a6) units. The monomers (a1) to (a6) may each be present alone or in combination of two or more kinds.

[0046] In the above polymerization, it is preferable to carry out the production by solution polymerization, since the acrylic resin (A) can be safely and stably produced with any monomer composition. It is particularly preferable to carry out the polymerization in an organic solvent, and the acrylic resin (A) polymerized in an organic solvent becomes an organic solvent-based acrylic resin.

[0047] Such solution polymerization may be carried out according to a conventional method, for example, by mixing or dropping copolymerization components such as the monomers (a1) to (a6) and a polymerization initiator into an organic solvent, and polymerizing the mixture under reflux or at 50 to 98° C. for 0.1 to 20 hours.

[0048] Specific examples of such polymerization initiators include azo-based polymerization initiators such as azobisisobutyronitrile and azobisdimethylvaleronitrile, which are normal radical polymerization initiators, and peroxide-based polymerization initiators such as benzoyl peroxide, lauroyl peroxide, di-t-butyl peroxide, and cumene hydroperoxide. These may be used alone or in combination of two or more. The amount of the polymerization initiator used is usually 0.001 to 5 parts by weight based on 100 parts by weight of the copolymerization components.

[0049] The weight-average molecular weight of the acrylic resin (A) thus obtained is usually 100,000 to 5,000,000, preferably 300,000 to 1,500,000, and particularly preferably 400,000 to 900,000. If the weight-average molecular weight is too small, the durability tends to decrease, and if it is too large, the adhesive strength tends to decrease.

[0050] The dispersity (weight average molecular weight / number average molecular weight) of the acrylic resin (A) is preferably 20 or less, particularly preferably 15 or less, further preferably 10 or less, and especially preferably 7 or less. If the dispersity is too high, the durability of the pressure-sensitive adhesive layer tends to decrease and foaming and the like tends to occur easily. The lower limit of the dispersity is usually 1.1 from the viewpoint of production limitations.

[0051] The weight average molecular weight of the acrylic resin (A) is a weight average molecular weight calculated based on the molecular weight of standard polystyrene. The weight average molecular weight was measured by a high performance liquid chromatograph (Waters Japan, "Waters 2695 (main body)" and "Waters 2414 (detector)") using a Shodex GPC KF-806L column (molecular weight exclusion limit: 2×10 7 , Separation range: 100~2×10 7The number average molecular weight is measured by using three columns in series (10000 / column, theoretical plate number: 10,000 plates / column, filler material: styrene-divinylbenzene copolymer, filler particle size: 10 μm), and the same method can be used for measuring the number average molecular weight.

[0052] The glass transition temperature (Tg) of the acrylic resin (A) is preferably from -80 to 10°C, particularly from -70 to -10°C, and further preferably from -65 to -20°C. If the glass transition temperature is too high, the tack tends to be insufficient, whereas if the glass transition temperature is too low, the heat resistance tends to decrease.

[0053] The above glass transition temperature (Tg) is a value calculated by applying the glass transition temperature and weight fraction of each of the monomers constituting the acrylic resin (A) as a homopolymer to the following Fox's formula.

[0054]

number

[0055] Here, the glass transition temperature when the monomer constituting the acrylic resin (A) is made into a homopolymer is usually a value measured by a differential scanning calorimeter (DSC) according to a method in accordance with JIS K7121-1987 or JIS K6240, or a value listed in a catalog.

[0056] The acrylic resin (A) is usually adjusted in viscosity with a solvent or the like and is used for coating as an acrylic resin (A) solution. The viscosity of the acrylic resin (A) solution is preferably 500 to 20,000 mPa·s / 25°C from the viewpoint of ease of handling, particularly preferably 1,000 to 18,000 mPa·s / 25°C, and more preferably 2,000 to 15,000 mPa·s / 25°C. If the viscosity is too high, the fluidity tends to decrease and handling becomes difficult, and if the viscosity is too low, coating of the adhesive tends to become difficult. The solution concentration during coating is usually 10 to 70% by weight.

[0057] The solvent is not particularly limited as long as it dissolves the acrylic resin (A), and examples thereof include ester solvents such as methyl acetate, ethyl acetate, methyl acetoacetate, and ethyl acetoacetate, ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, aromatic solvents such as toluene and xylene, and alcohol solvents such as methanol, ethanol, and propyl alcohol. Among these, ethyl acetate and methyl ethyl ketone, particularly ethyl acetate, are preferably used in terms of solubility, drying property, and price. These solvents may be used alone or in combination of two or more.

[0058] The viscosity of the acrylic resin (A) solution is measured by adjusting the temperature of the resin solution to 25° C. using a rotational viscometer method using a B-type viscometer.

[0059] <Crosslinking agent (B)> The pressure-sensitive adhesive composition of the present invention contains a crosslinking agent (B) in addition to the acrylic resin (A).

[0060] The crosslinking agent (B) reacts with the functional groups in the acrylic resin (A) to form a crosslinked structure. In particular, by using the epoxy crosslinking agent (b1) and the isocyanate crosslinking agent (b2) in combination, the effect of improving flame retardancy when a flame retardant is contained is increased. The reason for this is unclear, but it is believed that by using the epoxy-based crosslinking agent (b1) in combination with the isocyanate-based crosslinking agent (b2), it is possible to form an adhesive layer with a uniform crosslink density, and it is possible to impart flame retardant performance with the addition of a small amount of flame retardant. With only the epoxy-based crosslinking agent (b1), the crosslinked structure is hydrolyzed by the moisture generated during combustion, reducing the crosslink density, making it easier for combustion to continue, while with only the isocyanate-based crosslinking agent (b2), the crosslink density becomes non-uniform, resulting in insufficient flame retardant performance.

[0061] In addition, by using the epoxy-based crosslinking agent (b1) and the isocyanate-based crosslinking agent (b2) in combination, even a pressure-sensitive adhesive composition containing a flame retardant has a well-balanced adhesive performance between adhesion and holding power. The reason is not clear, but when the adhesive of the acrylic resin (A) containing the crosslinking agent (B) contains the flame retardant (C), the cohesive strength of the adhesive layer tends to decrease and the holding strength is greatly decreased, although it is not clear whether the flame retardant (C) behaves like a plasticizer. However, the present inventor has found that when the epoxy crosslinking agent (b1) and the isocyanate crosslinking agent (b2) are used in combination, even if the adhesive composition contains the flame retardant (C), a strong and dense crosslinked structure is formed, high cohesive strength is maintained, and holding strength is increased, and that by having the acrylic resin (A) have (meth)acrylic acid monomer (a1) units and hydroxyl group-containing monomer (a2) units, and if necessary, terminal carboxyl group-containing monomer (a3) ​​units, the adhesive layer becomes flexible and can maintain high peel strength even if a strong and dense crosslinked structure is formed.

[0062] Examples of the epoxy crosslinking agent (b1) include aliphatic epoxy crosslinking agents such as ethylene glycol diglycidyl ether, trimethylolpropane diglycidyl ether, and diglycidylamine; alicyclic epoxy crosslinking agents such as 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, and N,N,N',N'-tetraglycidyl-m-xylylenediamine; aromatic epoxy crosslinking agents such as diglycidylaniline; heterocyclic epoxy crosslinking agents such as 1,3,5-tris-(2,3-epoxybutyl)-isocyanurate, 1,3,5-tris-(3,4-epoxybutyl)-isocyanurate, and 1,3,5-tris-(4,5-epoxypentyl)-isocyanurate, among which alicyclic epoxy crosslinking agents are preferred. These can be used alone or in combination of two or more.

[0063] The isocyanate-based crosslinking agent (b2) contains at least two isocyanate groups, and examples thereof include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, and alicyclic polyisocyanates such as hydrogenated diphenylmethane diisocyanate, as well as their biuret and isocyanurate forms, and further adducts which are reaction products with low-molecular active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil. In particular, the adduct of tolylene diisocyanate and trimethylolpropane is preferred. These can be used alone or in combination of two or more.

[0064] The content of the epoxy crosslinking agent (b1) is 0.005 to 0.1 parts by weight, particularly 0.008 to 0.08 parts by weight, further 0.01 to 0.05 parts by weight, and particularly preferably 0.012 to 0.03 parts by weight, based on 100 parts by weight of the acrylic resin (A). If the content is too low, the holding power tends to decrease, and if it is too high, the adhesion to various adherends tends to decrease.

[0065] The content of the isocyanate crosslinking agent (b2) is 0.1 to 1.0 parts by weight, particularly 0.15 to 0.8 parts by weight, further 0.18 to 0.5 parts by weight, and particularly preferably 0.2 to 0.4 parts by weight, based on 100 parts by weight of the acrylic resin (A). If the content is too low, the holding power tends to decrease, and if the content is too high, the adhesiveness tends to decrease.

[0066] The content ratio of the epoxy-based crosslinking agent (b1) and the isocyanate-based crosslinking agent (b2) is preferably 2.5 to 25 parts by weight, more preferably 3.5 to 15 parts by weight, and even more preferably 5 to 10 parts by weight, of the epoxy-based crosslinking agent (b1) per 100 parts by weight of the isocyanate-based crosslinking agent (b2).

[0067] The above crosslinking agent can be used after being diluted with a solvent or the like, but the above content and content ratio indicate the actual content and content ratio of the crosslinking agent excluding the solvent and the like.

[0068] The present invention is characterized by using the crosslinking agents (b1) and (b2) in combination, but in some cases, other crosslinking agents may also be used in combination. Examples of other crosslinking agents that may be used in combination include aziridine crosslinking agents, melamine crosslinking agents, aldehyde crosslinking agents, amine crosslinking agents, and metal chelate crosslinking agents. These may be used alone or in combination of two or more types, but the effects of the present invention will not be achieved with a combination of crosslinking agents that do not include the (b1) or (b2) components.

[0069] Examples of the aziridine-based crosslinking agent include diphenylmethane-4,4'-bis(1-aziridinecarboxamide), trimethylolpropane tri-β-aziridinylpropionate, tetramethylolmethane tri-β-aziridinylpropionate, toluene-2,4-bis(1-aziridinecarboxamide), triethylenemelamine, bisisophthaloyl-1-(2-methylaziridine), tris-1-(2-methylaziridine)phosphine, trimethylolpropane tri-β-(2-methylaziridine)propionate, and the like.

[0070] Examples of the melamine-based crosslinking agent include melamine; methylolmelamine derivatives such as amino group-containing methylolmelamine, imino group-containing methylolmelamine, and hexamethylolmelamine obtained by condensing melamine with formaldehyde; and alkylated methylolmelamines such as partially or completely alkylated methylolmelamine and imino group-containing partially or completely alkylated methylolmelamine obtained by reacting a methylolmelamine derivative with a lower alcohol such as methyl alcohol or butyl alcohol to partially or completely etherify the methylolmelamine derivative.

[0071] Examples of the aldehyde crosslinking agent include aldehyde compounds that liberate aldehyde in an aqueous solution, such as formaldehyde, acetaldehyde, propionaldehyde, butylaldehyde, glyoxal, glutaraldehyde, dialdehyde starch, hexamethylenetetramine, 1,4-dioxane-2,3-diol, 1,3-bis(hydroxymethyl)-2-imidazolidine, dimethylol urea, N-methylol acrylamide, urea formalin resin, and melamine formalin resin, and aromatic aldehyde compounds, such as benzaldehyde, 2-methylbenzaldehyde, 4-methylbenzaldehyde, p-hydroxybenzaldehyde, and m-hydroxybenzaldehyde.

[0072] Examples of the amine-based crosslinking agent include 4,4'-methylene-bis(2-chloroaniline) (hereinafter abbreviated as "MOCA"), modified MOCA, and diethyltoluenediamine.

[0073] The above-mentioned metal chelate crosslinking agent can be, for example, chelate compounds whose metal atom is aluminum, zirconium, titanium, zinc, iron, tin, etc., and aluminum chelate compounds are preferred from the viewpoint of performance.As the aluminum chelate compounds, for example, diisopropoxyaluminum monooleyl acetoacetate, monoisopropoxyaluminum bisoleyl acetoacetate, monoisopropoxyaluminum monooleate monoethyl acetoacetate, diisopropoxyaluminum monolauryl acetoacetate, diisopropoxyaluminum monostearyl acetoacetate, diisopropoxyaluminum monoisostearyl acetoacetate, etc. can be mentioned.

[0074] <Flame retardant (C)> The flame retardant (C) used in the present invention may be any known flame retardant generally used as a flame retardant for adhesives, such as phosphorus-based flame retardants, metal hydroxyl-based flame retardants, metal phosphinate-based flame retardants, halogen-based flame retardants, a combination of a halogen-based flame retardant and antimony trioxide, nitrogen-containing compounds such as melamine cyanurate and triazine compounds, etc. These may be used alone or in combination of two or more kinds.

[0075] Examples of phosphorus-based flame retardants include non-halogen phosphate esters such as trimethyl phosphate, triethyl phosphate, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, cresyl diphenyl phosphate, 2-naphthyl diphenyl phosphate, and cresyl di-2,6-xylenyl phosphate; aromatic condensed phosphate esters such as "CR-733S," "CR-741," and "PX-200" manufactured by Daihachi Chemical Industry Co., Ltd.; non-halogen condensed phosphate esters such as "DAIGUARD-580," "DAIGUARD-610," and "DAIGUARD-880" manufactured by Daihachi Chemical Industry Co., Ltd.; amine phosphate salts such as melamine polyphosphate; and ammonium polyphosphate that is not coated with a resin or is coated with melamine or the like.

[0076] Among these, polyphosphates are preferred because they contain no halogen but have a high phosphorus concentration, making them highly flame retardant, and because even a small amount can be added to impart flame retardancy without reducing the adhesive properties. Of these, ammonium polyphosphate is preferred, and ammonium polyphosphate coated with melamine or the like is particularly preferred because it inhibits hydrolysis and has excellent resistance to moist heat.

[0077] Examples of metal hydroxyl group-based flame retardants include magnesium hydroxide and aluminum hydroxide.

[0078] Examples of the metal phosphinate flame retardant include "Exolit OP1230" and "Exolit OP930" manufactured by Clariant.

[0079] Examples of halogen-based flame retardants include bromine-based flame retardants such as tetrabromobisphenol A, hexabromocyclodecane, dibromodiphenyl oxide, tetrabromobisphenol A polycarbonate oligomer, brominated polystyrene, ethylene bistetrabromophthalimide, etc.; chlorine-based flame retardants such as chlorinated paraffin, perchlorocyclopentadecane, etc.; halogen-containing phosphate esters such as tris(tribromoneopentyl)phosphate, tris(chloropropyl)phosphate, etc.; and halogen-containing condensed phosphate esters such as "CR-504L", "CR-570", and "DAIGUARD-540" manufactured by Daihachi Chemical Industry Co., Ltd.

[0080] Among these, since halogen-containing flame retardants may generate toxic halogen gases or corrode metals when incinerated, it is preferable that the flame retardant (C) is a halogen-free flame retardant.

[0081] In addition, for example, in the case of a compound product (composite, composite material), it is said that a synergistic effect can be obtained by using a flame retardant (C) in combination with another flame retardant having a different mechanism of action rather than using the flame retardant alone. However, in the present invention, it is preferable to use the flame retardant alone from the viewpoint of not decreasing the adhesive strength or compatibility with the adhesive. In particular, the phosphorus-based flame retardants exemplified above are preferred, and ammonium polyphosphate coated with melamine or the like is particularly preferred, as it provides excellent flame retardancy with little deterioration in adhesive properties, and also inhibits hydrolysis and has excellent resistance to moist heat.

[0082] The content of the flame retardant (C) is preferably 1 to 100 parts by weight, more preferably 5 to 80 parts by weight, further preferably 7 to 60 parts by weight, further preferably 8 to 35 parts by weight, and particularly preferably 10 to 25 parts by weight, based on 100 parts by weight of the acrylic resin (A). If the content of the flame retardant (C) is too high, the adhesive properties of the adhesive tape tend to decrease, whereas if the content is too low, the flame retardancy tends to be insufficient.

[0083] <Tackifier (D)> The tackifier (D) is not an essential component, but is used to further exert the good physical properties of the acrylic resin (A), and is preferably contained in the adhesive composition of the present invention. Examples of the tackifier (D) include resins that are compatible with the acrylic resin (A), such as rosin-based resins, terpene-based resins, xylene-based resins, phenol-based resins, coumarone-based resins, and petroleum-based resins. These tackifiers (D) can be used alone or in combination of two or more. Among them, rosin-based resins, terpene-based resins, and petroleum-based resins are preferred.

[0084] Examples of the rosin resin include a rosin ester resin obtained by hydrogenating, disproportionating, dimerizing, and adding an acid to a raw rosin, and then esterifying the resultant with glycerin or pentaerythritol, and a rosin phenol resin obtained by adding phenol. Any of the rosin resins can be used to further exhibit the good physical properties of the acrylic resin (A). Among them, preferred are a disproportionated rosin ester obtained by disproportionating the raw rosin and esterifying it with glycerin or pentaerythritol, which has a softening point in the range of 70 to 130°C, a polymerized rosin ester obtained by dimerizing the raw rosin and esterifying it with pentaerythritol, which has a softening point in the range of 110 to 170°C, and a rosin phenol obtained by adding phenol to the raw rosin, which has a softening point in the range of 120 to 160°C.

[0085] The above terpene resin has the molecular formula (C5H8) nThe tackifier (D) used in the present invention is a resin obtained by homopolymerization or copolymerization of monoterpene (e.g., α-pinene, β-pinene, limonene, etc.) with a Friedel-Crafts catalyst. Specifically, examples of the resin obtained by homopolymerization or copolymerization of monoterpene include α-pinene resin, β-pinene resin, dipentene resin, terpene phenol resin, aromatic modified terpene resin, and hydrogenated terpene resin obtained by hydrogenating these resins. Among these, terpene phenol resins are preferred due to their good compatibility with the acrylic resin (A). Any of the terpene phenol resins will further enhance the good physical properties of the acrylic resin (A). In particular, those having a softening point of 90 to 170°C and a hydroxyl value in the range of 20 to 250 (mgKOH / g) are preferred, and those having a softening point of 100 to 150°C and a hydroxyl value in the range of 50 to 150 (mgKOH / g) are more preferred.

[0086] The petroleum resin is obtained, for example, by polymerization and further hydrogenation of C4-C5 and C9-C11 fraction monomers produced by thermal decomposition of naphtha, etc., and depending on the type of raw material fraction, examples include pure monomer resins, aliphatic (C5) petroleum resins, aromatic (C9) petroleum resins, hydrogenated petroleum resins, etc. Any of the petroleum resins can be used to further exhibit the good physical properties of the acrylic resin (A), but among them, those with a softening point in the range of 90 to 130°C are preferred, and it is further preferred to use a copolymerization system of a styrene monomer and an aliphatic monomer.

[0087] The content of the tackifier (D) is usually 1 to 50 parts by weight, particularly 5 to 30 parts by weight, and further preferably 5 to 20 parts by weight, per 100 parts by weight of the acrylic resin (A), and is appropriately blended depending on the required physical properties.

[0088] Furthermore, the pressure-sensitive adhesive composition of the present invention may contain, as other components, various additives such as resin components other than the acrylic resin (A), acrylic monomers, polymerization inhibitors, antioxidants, corrosion inhibitors, crosslinking accelerators, radical generators, peroxides, ultraviolet absorbers, plasticizers, pigments, stabilizers, fillers, and radical scavengers, metals, and resin particles, within the scope of the present invention. These may be used alone or in combination of two or more. In addition to the above, the pressure-sensitive adhesive composition may contain a small amount of impurities contained in the manufacturing raw materials of the components of the pressure-sensitive adhesive composition.

[0089] The content of the other components is preferably 5 parts by weight or less, more preferably 1 part by weight or less, and even more preferably 0.5 parts by weight or less, based on 100 parts by weight of the acrylic resin (A). The lower limit is usually 0 parts by weight. If the content is too high, the compatibility with the acrylic resin (A) decreases, and the durability tends to decrease. However, for additives (pigments, fillers, metals, resin particles, etc.) that do not exert their effects at the above content, an appropriate amount may be added within a range that exerts the effect of the additive while not inhibiting the effects of the present invention.

[0090] The pressure-sensitive adhesive composition of the present invention contains, as described above, the acrylic resin (A), the crosslinking agent (B), the flame retardant (C), and, if necessary, a tackifier (D) and further other components. The method for producing the pressure-sensitive adhesive composition of the present invention is not particularly limited. In addition to the commonly known mechanical kneading dispersion method, known methods such as a solvent dispersion method and an ultrasonic dispersion method can be used as necessary.

[0091] The adhesive composition of the present invention can be obtained by mixing the above-mentioned components. The adhesive composition is crosslinked to obtain the adhesive of the present invention. The adhesive can be applied to various substrates to be used as an adhesive for adhesive tapes, and is particularly suitable for use as an adhesive layer for flame-retardant adhesive tapes.

[0092] The pressure-sensitive adhesive composition of the present invention preferably has a gel fraction of 30% by weight or more when crosslinked, from the viewpoint of increasing the holding power, more preferably 35% by weight or more, and particularly preferably 40% by weight or more. In order to make the gel fraction equal to or more than the lower limit, the type and content of the epoxy-based crosslinking agent (b1) and the isocyanate-based crosslinking agent (b2) may be adjusted, and the upper limit of the gel fraction is preferably 70% by weight or less, more preferably 60% by weight or less, and particularly preferably 50% by weight or less. If the gel fraction is too low, the holding power tends to decrease, and if the gel fraction is too high, the peel strength tends to decrease.

[0093] <Adhesive tape> The pressure-sensitive adhesive tape of the present invention contains the pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition as a pressure-sensitive adhesive layer. Specifically, the pressure-sensitive adhesive composition is dissolved in a solvent such as ethyl acetate to prepare a pressure-sensitive adhesive composition solution for coating so that the solid content concentration is 10 to 70% by weight, and the solution is applied to a substrate and dried to form a pressure-sensitive adhesive tape. The pressure-sensitive adhesive composition prepared as above is an organic solvent-based pressure-sensitive adhesive composition.

[0094] Such an adhesive tape may be produced by a known method for producing an adhesive tape, for example, by coating one side of a substrate with an adhesive and drying it, and then overlaying a release liner on the surface of the formed adhesive layer, or by coating one side of a release liner with an adhesive and drying it, and then overlaying a substrate on the surface of the formed adhesive layer. Among these, the method of coating one side of a release liner with an adhesive and drying it, and then overlaying a substrate on the surface of the formed adhesive layer is preferred from the viewpoint of handling, etc.

[0095] The substrate is preferably hand-tearable, and the surface of the substrate having hand-tearability may be appropriately subjected to a known and commonly used surface treatment, for example, a physical treatment such as a corona discharge treatment or a plasma treatment, or a chemical treatment such as a primer treatment.

[0096] The substrate is not particularly limited as long as it is a conventionally known substrate, and examples thereof include rayon cloth, cotton cloth, polyester cloth, cloth made of blended yarn of rayon and polyester, nonwoven fabric, flat yarn cloth, laminated film in which a plastic film is laminated on a flat yarn cloth, etc. Among these, those containing flat yarn cloth are preferred because of their high tensile strength in the longitudinal direction.

[0097] Flat yarn cloth is a woven fabric made by cutting polyethylene or polypropylene film called flat yarn into strips and stretching it to give it strength, then weaving the flat yarns into a fabric. The intersections of the flat yarns that cross vertically and horizontally of this woven fabric are fixed by heat fusion to prevent misalignment.

[0098] Examples of the release liner include plastic films made of plastics such as polyolefin resins such as polyethylene, polyester resins such as polyethylene terephthalate, vinyl acetate resins, polyimide resins, fluorine resins, and cellophane; paper such as kraft paper and Japanese paper; rubber sheets made of natural rubber, butyl rubber, and the like; foam sheets obtained by foaming polyurethane, polychloroprene rubber, and the like; metal foils such as aluminum foil and copper foil; composites of these, etc. Furthermore, these may be subjected to a surface treatment such as a corona treatment on one or both sides.

[0099] Further, examples of the release liner include paper obtained by laminating a film such as polyethylene onto glassine paper, craft paper, or clay-coated paper; paper coated with a resin such as polyvinyl alcohol or an acrylic acid ester copolymer; and synthetic resin films such as polyester or polypropylene coated with a release agent such as a fluorine-based resin or a silicone-based resin. These can be used alone or in combination of two or more.

[0100] Among these, paper release liners are preferred because they are easily torn by hand, and the basis weight of the base paper is 40 to 120 g / m2 , preferably 50 to 80 g / m 2 Particularly preferred is a paper release liner having a thickness of 40 to 180 μm, particularly 60 to 140 μm, and further preferably 80 to 120 μm. If the thickness is too thin, wrinkles may occur during winding, making production difficult, while if the thickness is too thick, hand tearability may decrease.

[0101] The coating device used when coating one side of the above-mentioned substrate or release liner with the adhesive may be any commonly used coating device, such as a roll knife coater, die coater, roll coater, bar coater, gravure roll coater, reverse roll coater, dipping, blade coater, etc.

[0102] The thickness of the pressure-sensitive adhesive layer after drying is preferably from 5 to 200 μm, particularly preferably from 10 to 150 μm, and further preferably from 15 to 130 μm. If the thickness is too thick, it tends to be difficult to apply the adhesive, whereas if the thickness is too thin, sufficient adhesive strength tends to be difficult to obtain.

[0103] The pressure-sensitive adhesive tape of the present invention may be a single-sided pressure-sensitive adhesive tape or a double-sided pressure-sensitive adhesive tape. The pressure-sensitive adhesive layers of the double-sided pressure-sensitive adhesive tape may be the same pressure-sensitive adhesive layer or may be pressure-sensitive adhesive layers having different compositions.

[0104] In addition, when a release liner is laminated on the adhesive layer of the double-sided adhesive tape, it is preferable to select the release liners laminated on both sides so that their peel strengths are different in order to improve workability. For example, the workability is improved by selecting a release liner that has a smaller peel strength on the side of the double-sided adhesive tape that is first applied than on the side of the double-sided adhesive tape that is next applied.

[0105] The drying conditions may be any conditions under which the solvent and residual monomers in the adhesive are dried and removed during drying, and when a crosslinking agent (B) is used, the functional group of the acrylic resin (A) reacts with the crosslinking agent (B) to form a crosslinked structure. For example, drying conditions are preferably 60 to 120°C and about 1 to 5 minutes. After drying, the adhesive layer is sandwiched between sheet-like substrates and aged to further promote the crosslinking reaction.

[0106] The pressure-sensitive adhesive tape of the present invention may be in the form of a roll or in the form of sheets, or may be further processed into various shapes. When the adhesive tape is a double-sided adhesive tape in a sheet state, it is preferable that a release liner be provided on the surface of both of the two adhesive layers, and when it is in a roll state, it is preferable that a release liner be provided on the surface of only one of the two adhesive layers.

[0107] The adhesive tape of the present invention is thus obtained, and the adhesive tape of the present invention does not lose its adhesive properties even when applied to an adherend or substrate that would otherwise cause a loss of adhesive properties, and has good holding power. Furthermore, when a substrate having hand-tearability is used as the substrate film, the tape can be easily cut by hand at any desired position in the width direction of the tape without using a tape cutter or the like, making the tape particularly useful as an adhesive tape.

[0108] The adhesive strength of the adhesive layer in the above-mentioned adhesive tape is preferably such that the 180° peel strength in accordance with JIS Z0237 against the adherend to be used is 1 to 100 N / 25 mm.

[0109] In particular, when a test plate made of SUS304 stainless steel, which has a relatively high polarity, is used as the adherend, the 180° peel strength is preferably 25 N / 25 mm or more, particularly preferably 30 N / 25 mm or more, and further preferably 35 N / 25 mm or more. The upper limit is usually about 100 N / 25 mm.

[0110] The adhesive strength varies depending on the composition (material) and surface condition (surface roughness) of the adherend, treatment (cleaning) conditions, etc., and is not limited to the above peel strength range.

[0111] The adhesive strength is a value measured in accordance with JIS Z 0237. Specifically, it can be measured by the method described in the Examples below.

[0112] If the test piece is a double-sided adhesive tape, the adhesive side not being tested can be measured by covering it with a polyethylene terephthalate film (Lumirror S10, manufactured by Toray Industries, Inc.) having a nominal thickness of 25 μm as specified in JIS C2318.

[0113] Furthermore, when the holding power of the pressure-sensitive adhesive layer in the pressure-sensitive adhesive tape of the present invention is measured by the <Method for measuring holding power> below, specifically the method described in the Examples below, it is particularly preferable that the test piece does not fall off the test plate after 24 hours (1,440 minutes) has elapsed, and even if the test piece falls within 24 hours, the holding time is preferably 100 minutes or more, more preferably 150 minutes or more, and particularly preferably 500 minutes or more. <Method of measuring holding power> The adhesive tape was cut to a width of 25 mm and a length of 75 mm, and the adhesive layer of the tape was pressed against a SUS plate so that the contact area between the tape and the plate was 25 mm wide x 25 mm long. A 1000g weight was then attached to the SUS plate so that the adhesive tape was hanging vertically from the plate, and the time it took for the tape to fall was then measured in an environment of 40°C.

[0114] Furthermore, the gel fraction of the adhesive layer in the above adhesive tape is preferably 30 to 70% by weight, more preferably 35 to 60% by weight, and particularly preferably 40 to 50% by weight, from the viewpoints of adhesion and holding power. If the gel fraction is too low, the holding power to the adherend tends to decrease, and if it is too high, the adhesion to the adherend tends to decrease. The gel fraction is in the preferred range, and an adhesive composition using an epoxy-based crosslinking agent (b1) and an isocyanate-based crosslinking agent (b2) in combination is preferred in that it has a good balance between adhesion and holding power at a high level, and is easy to stably maintain a high holding power even when exposed to high temperature and high humidity.

[0115] The gel fraction is an indicator of the degree of crosslinking (degree of curing) and can be measured, for example, by the method described in the Examples below.

[0116] The gel fraction of the pressure-sensitive adhesive can be adjusted to fall within the above range by adjusting the type and amount of the crosslinking agent (B), for example.

[0117] In addition, the adhesive tape of the present invention is preferably one having a large tensile strength, and is required to have a strength necessary for pulling it without distortion when attaching it to an adherend or peeling it off for position correction. The tensile strength of the adhesive tape is preferably 20N / 25mm or more, more preferably 30N / 25mm or more, and even more preferably 40N / 25mm or more. The upper limit of the tensile strength is usually 250N / 25mm. To obtain an adhesive tape with a large tensile strength, a film having a tensile strength of the base film equal to or greater than that of the desired adhesive tape can be used.

[0118] The pressure-sensitive adhesive tape of the present invention has flame retardancy and is excellent in both adhesion and retention.Therefore, it can be used in a wide range of applications, such as packaging tapes such as flame-retardant adhesive tapes, flame-retardant adhesive tapes, craft tapes, OPP tapes, and cloth adhesive tapes, cellophane adhesive tapes for light packaging, foam tapes for automobiles, vibration-damping sheets, protective tapes for housing, soundproofing seals, double-sided tapes for fixing carpets, vinyl tapes for electrical insulation, outdoor anticorrosive tapes, tapes for indoor displays, slip prevention tapes, adhesive tapes for airtight waterproofing, adhesive substrates for medical first aid bandages, surgical tapes, adhesive bandages, tapes for electrical and electronic equipment, double-sided tapes for optics, dicing tapes for semiconductors, thermal conductive tapes, heat-resistant tapes, conductive tapes, etc.

[0119] Furthermore, the pressure-sensitive adhesive tape can be used particularly for construction applications, for example, for housing structures and their components, and for gaps between components, and can therefore be suitably used as an airtight and waterproof pressure-sensitive adhesive tape. EXAMPLES

[0120] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are by weight.

[0121] First, various acrylic resins (A) were prepared as follows. The weight average molecular weight, dispersity, glass transition temperature, and viscosity of the acrylic resin (A) were measured according to the methods described above.

[0122] <Acrylic resin (A)> Prior to the production of the acrylic resin (A), the following were prepared as copolymerization components (a) to be used in the production. Component (a1) Acrylic Acid (a2) Component 2-Hydroxyethyl methacrylate (a3) Component A monomer having a terminal carboxyl group represented by the following general formula (2): CH2=CR 1 -CO-O-(R 2 -COO-) n H (2) In the above general formula (2), R 1 is hydrogen, R 2 is an ethylene chain, n is 1 to 5 (a4-1) Component n-Butyl acrylate (a4-2) Component 2-Ethylhexyl acrylate (a5-1) Component Methyl acrylate (a5-2) Component Vinyl acetate

[0123] For the above component (a3), "Sipomer H" manufactured by Solvay Nicca was used. Sipomer H is R of the above general formula (2) 1 is hydrogen, R 2 is an ethylene chain, n = 1 compound (a3-1) is 56%, R 1 is hydrogen, R 2 The mixture contains 16.1% of the compound (a3-2) having an ethylene chain and n=2 to 5, and 27.9% of acrylic acid (a1) (hereinafter, R 1 is hydrogen, R 2 is an ethylene chain, and compounds with n = 1 to 5 are sometimes referred to as "CAO").

[0124] [Production of acrylic resin (A-1)] In a reactor equipped with a thermometer, a stirrer, and a reflux condenser, 5 parts of Sipomer H [3.6 parts of CAO (a3), 1.4 parts of acrylic acid (a1)], 0.1 parts of 2-hydroxyethyl methacrylate (a2), 25.8 parts of n-butyl acrylate (a4-1), 63.1 parts of 2-ethylhexyl acrylate (a4-2), 6 parts of methyl acrylate (a5-1), 55 parts of ethyl acetate as a solvent, and 0.15 parts of azobisisobutyronitrile as a polymerization initiator were charged as copolymerization components, and the temperature was raised with stirring. Polymerization was carried out for 7 hours at the reflux temperature of the ethyl acetate (mixture), and the reaction mixture was diluted with ethyl acetate to obtain an acrylic resin (A-1) solution with a solid content of 56% and a viscosity of 7000 mPa·s / 25°C. The weight average molecular weight of the obtained acrylic resin (A-1) was 620,000, the dispersity was 5.8, and the glass transition temperature was -59°C.

[0125] [Production of acrylic resin (A-2)] In a reactor equipped with a thermometer, a stirrer, and a reflux condenser, 0.1 parts of 2-hydroxyethyl methacrylate (a2), 2.9 parts of acrylic acid (a1), 46 parts of n-butyl acrylate (a4-1), 46 parts of 2-ethylhexyl acrylate (a4-2), 5 parts of vinyl acetate (a5-2), 40 parts of ethyl acetate as a solvent, and 0.1 parts of azobisisobutyronitrile as a polymerization initiator were charged, and the temperature was raised with stirring. Polymerization was carried out for 9 hours at the reflux temperature of the ethyl acetate (mixture), and the reaction mixture was diluted with toluene to obtain an acrylic resin (A-2) solution with a solid content of 45%. The weight average molecular weight of the obtained acrylic resin (A-2) was 600,000, the dispersity was 4.8, the viscosity was 7,500 mPa·s / 25°C, and the glass transition temperature was -57°C.

[0126] <Crosslinking agent (B)> The following was prepared as the crosslinking agent (B). Epoxy crosslinking agent (b1): Tetrad C (1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane), manufactured by Mitsubishi Gas Chemical Company, Inc. Isocyanate-based crosslinking agent (b2): Tosoh Corporation, Coronate L-55E (solid content 55%)

[0127] <Flame retardant (C)> The following was prepared as a flame retardant (C): Melamine resin-coated ammonium polyphosphate (type II) flame retardant: BUDENHEIM, TERRAJU C-80

[0128] <Tackifier (D)> The following tackifiers (D) were prepared: Disproportionated rosin ester: Arakawa Chemical Industries, Super Ester A-100 (glycerin ester of disproportionated rosin, softening point 95-105°C)

[0129] <Example 1> For the acrylic resin (A) solution prepared as described above, 0.018 parts of epoxy-based crosslinking agent (b1) (Tetrad C) converted to solids (resin content), 0.29 parts of isocyanate-based crosslinking agent (b2) (Coronate L-55E) converted to solids (resin content), 24 parts of flame retardant (C), and 15 parts of tackifier (D) were mixed with 100 parts of the solids (resin content), and the solution was adjusted with ethyl acetate to a solids concentration of 40%, and stirred until uniform, to obtain a solution of an adhesive composition.

[0130] <Examples 2 to 4, Comparative Examples 1 to 4> The same procedure as in Example 1 above was carried out except that the components of the adhesive composition were changed as shown in Table 1 below, to obtain adhesive composition solutions of Examples 2 to 4 and Comparative Examples 1 to 4.

[0131] For the obtained pressure-sensitive adhesive compositions of Examples 1 to 4 and Comparative Examples 1 to 4, pressure-sensitive adhesive tapes were produced as described below and the following evaluations were carried out. The evaluation results are shown in Table 1 below.

[0132] [Preparation of adhesive tape] The adhesive composition solution prepared as described above was applied to the release surface of a paper release liner [SS-70-SBX (Shinomura Chemical Industry)] using an applicator so that the thickness after drying would be 100 μm, and then it was dried at 80° C. for 5 minutes, and flat yarn (Diatex, thickness 130 μm) was attached. Then, it was subjected to heat aging treatment in a dryer at 40° C. for 7 days to prepare an adhesive tape.

[0133] <Gel fraction> A 200-mesh SUS wire mesh large enough to encase the resulting adhesive tape is prepared and its weight is measured (1). The paper release liner is peeled off from the adhesive tape and wrapped in the aforementioned SUS wire mesh, and the weight of the tape together with the wire mesh is measured (2). After immersion in toluene maintained at 23°C for 48 hours, it is thoroughly dried and the weight of the tape together with the wire mesh is measured (3). After immersion, the tape is removed from the wire mesh, the remaining adhesive layer is removed, and the weight of the base material is measured (4). Subtraction is performed as shown in the following formula, and the weight percentage of the adhesive component after immersion compared to before immersion is determined as the gel fraction. [Formula] Gel fraction (wt%) = (weight of tape after immersion including weight of SUS wire mesh (3) - weight of substrate (4) - weight of SUS wire mesh (1)) / (weight of tape before immersion including weight of SUS wire mesh (2) - weight of substrate (4) - weight of SUS wire mesh (1)) x 100

[0134] <180° peel strength> The above adhesive tape was cut to a width of 25 mm and a length of 150 mm to prepare a test piece. In addition, a test plate made of SUS304 steel, which had been polished with water-resistant sandpaper (#360), was used as an adherend after the surface was washed with ethyl acetate and left to stand overnight in an atmosphere of 23°C and 50%RH. The paper release liner was peeled off from the above test piece, and the adhesive layer of the test piece was pressed onto the above test plate by a roller weighing 2 kg, which was moved back and forth once at a pressing speed of 5 mm / sec. After pressing, the test piece was left to stand for 20 minutes in an atmosphere of 23°C and 50%RH, the play part of the test piece was folded back by 180° and peeled off by 30 mm, and then the test plate was fixed to the lower chuck of the peel strength tester and the end of the test piece was fixed to the upper chuck in the same atmosphere, and the adhesive tape was peeled off from the adherend at a peel angle of 180° and a speed of 300 mm / min, and the peel strength was measured.

[0135] <Holding power> The above adhesive tape was cut to a width of 25 mm and a length of 75 mm to prepare a test piece. In addition, a test plate made of SUS304 steel, which had been polished with waterproof sandpaper (#360), was used as an adherend after the surface was washed with ethyl acetate and left to stand overnight in an atmosphere of 23°C and 50% RH. The above test piece was pressed against the test plate by a roller weighing 2 kg, which was reciprocated at a pressing speed of 5 mm / sec once, so that the contact area between the adhesive layer of the test piece, from which the paper release liner had been peeled off, and the test plate was 25 mm wide x 25 mm long. In addition, the part of the test piece where the adhesive was exposed was folded back. After pressing, the test piece was left to stand for 30 minutes in an environment of 23°C and 50% RH, and then moved to an environment of 40°C and left to stand for 20 minutes. A weight of 1000 g was attached to the test plate so that the test piece was hanging vertically, and the time it took for the test piece to fall was measured in an environment of 40°C. If the test piece did not fall after 24 hours (1,440 minutes), the test was deemed to be longer than 1,440 minutes.

[0136] <Flame retardant (EN13501-1 ISO11925-2)> The above adhesive tape was used to evaluate flame retardancy in accordance with ISO11925-2, an ignition test standard stipulated in the European building material fire safety standard EN13501-1. Since this was an evaluation of the adhesive tape alone, it was judged based on whether it passed the evaluation equivalent to CLASS B / C / D. The evaluation was judged based on three items: average burning length (150mm or less is a pass), presence or absence of burning drops (no burning drops is a pass), and presence or absence of completely burned samples (no completely burned samples is a pass, sample length is 250mm). Those that passed all items were deemed to have passed flame retardancy, and those that failed even one item were deemed to have failed.

[0137] <Airtightness and waterproofness test> Using the above adhesive tape, a nail driving water leakage test was carried out in accordance with AAMA711-13 5.2. Test pieces that showed no water leakage were rated as passed, and test pieces that showed water leakage were rated as failed.

[0138] [Table 1]

[0139] From the results in Table 1 above, the example products of the present invention in which the epoxy-based crosslinking agent (b1) and the isocyanate-based crosslinking agent (b2) were used in combination were excellent in flame retardancy.

[0140] In contrast, Comparative Examples 1 and 2, which used only the isocyanate-based crosslinking agent (b2) as the crosslinking agent (B), and Comparative Examples 3 and 4, which used only the epoxy-based crosslinking agent (b1), had insufficient flame retardancy. Comparative Example 1, which did not use the flame retardant (C), had high peel strength and did not show a significant decrease in holding power, but Comparative Example 2, which added the flame retardant (C), showed a significant decrease in holding power.

[0141] In other words, it can be seen that an adhesive tape using an adhesive composition containing an acrylic resin (A) obtained by copolymerizing a copolymerization component (a) containing a (meth)acrylic acid monomer (a1) and a hydroxyl group-containing monomer (a2), an epoxy-based crosslinking agent (b1), an isocyanate-based crosslinking agent (b2) and a flame retardant (C) has excellent flame retardancy, as well as excellent adhesion and holding power, and thus has an excellent balance of adhesive properties.

[0142] Furthermore, none of the above adhesive tapes were found to leak in the AAMA nailing leakage test, and they can be used, for example, in the structures of houses, their components, and in the gaps between components, making them suitable for use as airtight waterproof adhesive tapes.

[0143] In the above embodiment, specific embodiments of the present invention are shown, but the above embodiment is merely illustrative and should not be interpreted as being limiting. Various modifications that are obvious to those skilled in the art are intended to be within the scope of the present invention. [Industrial Applicability]

[0144] The adhesive composition of the present invention is excellent in flame retardancy, and is also excellent in both adhesion and retention.Therefore, it can be used in a wide range of applications, such as packaging tapes such as craft tapes, OPP tapes, and cloth adhesive tapes, cellophane adhesive tapes for light packaging, foam tapes for automobiles, vibration-damping sheets, flame-retardant adhesive tapes, flame-retardant adhesive tapes, protective tapes for housing, soundproofing seals, double-sided tapes for fixing carpets, vinyl tapes for electrical insulation, outdoor anticorrosive tapes, tapes for indoor displays, slip prevention tapes, adhesive tapes for airtight waterproofing, adhesive substrates for medical first aid bandages, surgical tapes, adhesive bandages, tapes for electrical and electronic equipment, double-sided tapes for optics, dicing tapes for semiconductors, thermal conductive tapes, heat-resistant tapes, conductive tapes, etc.

Claims

1. The pressure-sensitive adhesive composition comprises an acrylic resin (A) containing 0.1 to 5 wt % of (meth)acrylic acid monomer (a1) units and 0.01 to 5 wt % of hydroxyl group-containing monomer (a2) units, an epoxy crosslinking agent (b1), an isocyanate crosslinking agent (b2), and a phosphorus-based flame retardant (C).

2. The pressure-sensitive adhesive composition according to claim 1 , wherein the acrylic resin (A) contains a terminal carboxyl group-containing monomer (a3) ​​unit represented by the following general formula (1): 【Chemistry 1】 Here, R 1 is hydrogen or a methyl group, R 2 represents a divalent saturated aliphatic group, an unsaturated aliphatic group, an aromatic group, a saturated alicyclic group, or an unsaturated alicyclic hydrocarbon group, and n represents a positive number of 1 or more.

3. The pressure-sensitive adhesive composition according to claim 2, wherein the acrylic resin (A) is an acrylic resin having the following monomer units (a1) to (a4): (a1) (meth)acrylic acid monomer unit: 0.1 to 5% by weight (a2) Hydroxyl group-containing monomer unit: 0.01 to 5% by weight (a3) 1 to 20% by weight of a terminal carboxyl group-containing monomer unit represented by the above general formula (1) (a4) (meth)acrylate monomer units having an alkyl group having 4 to 24 carbon atoms: 55 to 97% by weight

4. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, wherein the content of the flame retardant (C) is 1 to 100 parts by weight per 100 parts by weight of the acrylic resin (A).

5. A pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition according to any one of claims 1 to 4.

6. An adhesive tape comprising a substrate and the adhesive according to claim 5 formed on the substrate.

7. 7. An airtight and waterproof pressure-sensitive adhesive tape comprising the pressure-sensitive adhesive tape according to claim 6.

Citation Information

Patent Citations

  • Flame-retardant adhesive tape

    JP2008024827A

  • Dicing tape with die attach film, and method of manufacturing semiconductor apparatus

    JP2010263041A

  • Flame-retardant pressure-sensitive adhesive composition, flame-retardant pressure-sensitive adhesive tape and flame-retardant pressure-sensitive adhesive sheet

    JP2012167160A

  • Adhesive composition

    JP2013177510A

  • Flame resistant adhesive composition, flame resistant adhesive tape and flame resistant adhesive sheet

    WO2011111534A1